2022
DOI: 10.3389/fphar.2022.950035
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of p38 mitogen-activated protein kinase inhibitors (MAPKIs) in COPD

Abstract: Introduction: Chronic inflammation is the core mechanism of the development of chronic obstructive pulmonary disease (COPD). Corticosteroid resistance in COPD limits its anti-inflammatory potency. p38 MAPKIs were suggested as an alternative to corticosteroids despite the fact that there is currently no systematic review evaluating existing evidence.Methods: This randomized controlled trials (RCT)-based systematic review with meta-analysis was conducted following the PRISMA statement. RCTs were searched and scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…For ethical reasons, we have tested only p38 inhibition in the mouse model, and here, we confirmed that systemic pretreatment with SB203580 preventively attenuated MHV-68 reactivation induced by pulmonary CNP exposure. Thus, p38 might serve as potential therapeutic target in emphysematous CLDs related to ambient particle exposure, and p38 inhibition is already a drug target for chronic inflammatory lung diseases such as COPD. , Even if the results of clinical trials evaluating p38 MAPK inhibitors as drugs for COPD therapy are currently controversial, this could be different for COPD observed in never-smokers where exposure and mechanisms of disease development might differ as well.…”
Section: Discussionmentioning
confidence: 99%
“…For ethical reasons, we have tested only p38 inhibition in the mouse model, and here, we confirmed that systemic pretreatment with SB203580 preventively attenuated MHV-68 reactivation induced by pulmonary CNP exposure. Thus, p38 might serve as potential therapeutic target in emphysematous CLDs related to ambient particle exposure, and p38 inhibition is already a drug target for chronic inflammatory lung diseases such as COPD. , Even if the results of clinical trials evaluating p38 MAPK inhibitors as drugs for COPD therapy are currently controversial, this could be different for COPD observed in never-smokers where exposure and mechanisms of disease development might differ as well.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of COPD, p38 inhibition has been observed to effectively mitigate inflammation and oxidative stress in the pulmonary and muscular tissues of affected individuals, which are closely associated with airflow restriction, respiratory distress, and reduced physical tolerance [55,174]. Moreover, the p38 inhibitors have demonstrated the capability to improve key lung function parameters and alleviate dyspnea in COPD patients, as assessed through measurements such as forced expiratory volume in 1 s (FEV1), forced vital capacity (FVC), and transition dyspnea index (TDI) [175].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the p38 inhibitors have demonstrated the capability to improve key lung function parameters and alleviate dyspnea in COPD patients, as assessed through measurements such as forced expiratory volume in 1 s (FEV1), forced vital capacity (FVC), and transition dyspnea index (TDI) [175]. Notably, p38 inhibitors appear to offer superior therapeutic outcomes compared to steroids for specific subsets of COPD patients, given that steroids possess limited antiinflammatory efficacy and are not recommended as standalone treatments for COPD [55,174]. However, it is important to acknowledge that p38 inhibitors may entail undesirable adverse effects, including liver toxicity and cutaneous reactions, which impose restrictions on their clinical usage and raise concerns regarding their safety [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral administration of this class of drugs at safe doses is likely insufficient to induce significant clinical benefit. 60 However, inhaled p38 MAPK inhibitors may lead to a higher local drug concentrations in the lung. An alternative approach could be the development of selective inhibitors of the α-δ subgroups.…”
Section: Inhibition Of Recruitment and Activation Of The Inflammatory...mentioning
confidence: 99%